DOES ADVANCE CARE PLANNING TRANSLATE INTO IMPROVED CARE IN A RURAL WESTERN AUSTRALIAN HOSPITAL SETTING?. Issue 2 (1st June 2013) - Auret, K; Sinclair, C; Averill, B; Evans, S F
Abstract : Background: Western Australia (WA) passed legislation supporting formal advance care planning (ACP) in 2010, allowing Advance Health Directive (AHD) and Enduring Power of Guardianship (EPG) forms. It is timely to audit the quality of end-of-life care provided in a rural area. Aim: Report ACP uptake and impact on end-of-life care in a rural hospital setting. Methods: This retrospective case notes-based audit of 90 admissions resulting in death was conducted in five rural hospitals in the Great Southern region of WA in 2012: the 100-bed regional centre (N=50) and four more remote ∼10-bed facilities (N=10). A palliative care nurse used an in-house designed audit tool to collect data on demographics, process and outcomes measures. A palliative physician double coded five randomly selected sets of notes. Results: Most patients elderly (M=79.6 years), admitted via ED (58%), on average 13 days before death. Malignancy accounted for 40% of deaths. Some form of ACP was documented in 34%, with 9% having an AHD and 1% having an EPG. 50% died on the Liverpool end-of-life care pathway, those on the pathway scored higher on a composite measure of care quality (χ 2 (2, 90)=31.6, p<0.001). ACP documentation did not predict likelihood of being commenced on the pathway (p>0.05) or scores on the composite measure (p>0.05). Discussion: As ACP is promoted in our community, our rural hospital network must develop system-wide responses to guarantee ACP influences care. Conclusion: This audit reports baseline data, which can be repeated following ACP-based interventions.